Students’ mathematical creative thinking ability in creative problem solving learning based on self-esteem - Wicahyono, Dangu Prastiyo; Asikin, Mohammad; Suhito, Suhito (Department of Mathematics, Universitas Negeri Semarang, 2018)
The purpose of this study was to determine the improvement of students’ mathematical creative thinking ability and to describe students’ mathematical creative thinking ability based on self-esteem. The method used in this study was mixed methods. The population in this study were seventh grade students in one of the junior high school in Semarang City. Through simple random sampling, the reseachers chose class VII A as an experimental class. Futhermore, 6 study subjects were interviewed consisted, covering 3 subjects from high self-esteem level and 3 subjects from low self-esteem level. The results of this study were: (1) student’s mathematical creative thinking ability increased with a gain index of 0,4 and was included in medium level; (2) students with the high self-esteem level were categorized in level 4 of TBKM; and (3) students with the low self-esteem level were grouped in level 0 TBKM.